Voltage/mass ratio (VMR) prognosis value in heart failure (HF) patients with transthyretin cardiac amyloidosis (ATTR-CA). (25th January 2023) - Costa, J; Pierre, M; Nazeyrollas, P
Abstract: Funding Acknowledgements: Type of funding sources: None. Introduction: Transthyretin cardiac amyloidosis (ATTR-CA) is an emerging cause of heart failure (HF) and is associated with cardiac mass hypertrophy and voltage impairment, but little is known on how theses markers interplay with survival. Objective: To evaluate if cardiac voltage/mass ratio (VMR) is associated with prognosis in HF patients involving ATTR-CA. Methods: Patients with confirmed mutated (m) or wild-type (wt) ATTR-CA addressed in a single cardiology center underwent retrospective ECG and echocardiographic study to define voltage with Sokolow indice (SV1+RV5, in mV) and left ventricular mass (LVM, g/m²) according to ASE definition. Two groups of patients were defined according to the median cardiac voltage/mass ratio (VMR in µV/g/m²) : Low (VMR < 6.1) or normal (VMR ≥ 6.1). Tc99m-HDP myocardial uptake (MU) on bone scintigraphy (BS) was described according to Perugini (P) classification : PI (MU < chest bones), PII (MU = chest bones) and PIII (MU > bones). Main end-point was overall mortality. Results: Among the 74 patients included, mean age was 82±7 years, 80% were males (Graph 1) and 25 (34%) were classified as ATTRwt-CA, 3 (4%) as ATTRm-CA, and 46 (62%) had ongoing genetic exploration. Mean follow-up was 543±332 days. Overall mortality was 21%. On BS, 6 patients (8%) were ranked as PI, 30 (42%) PII and 36 (50%) PIII, with no difference on mortality rates. After ANOVA, mean VMRi significantly decreased with intensity of Tc99m-HDP myocardial uptake on BS (p=0.033, Graph 2A). After log-rank test, survival was impaired in the low VMR group (p=0.034, Graph 2B). After Cox regression, low voltage/masse ratio remained associated with increased risk of mortality (HR 4.6, 95% CI [1.1–18.6], p=0.03), after adjusting on age, sex, left ventricle ejection fraction and log(NT-proBNP). Conclusion: VMR is a simple index to collect and significantly associated with impaired survival in HF patients with ATTR-CA. Further studies are needed to confirm these results. Graph1. AC-TTR patients characteristics. Graph2. VMRi prognosis value.